Chances of the rbcL Gene as DNA Barcode Based on Chloroplast DNA to Uncoverthe Genetik Diversity of Local Indonesian Black Rice (Oryza sativa L.) - Abdul Basith (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Black rice (Oryza sativa L.) is one of germ plasm where there are many found in Indonesia. The popularity of black rice growing in line with public awareness for consuming a functional food. But the scientific study of black rice germ plasm in Indonesia still classified as low, especially the scientific study of the molecular genetik diversity. Information of molecular genetik diversity adequately on black rice germ plasm is one of the cornerstone for the development of action strategies for conservation the varieties of black rice in Indonesia in a sustainable way. The scientific study which is expected to be implemented in the form of research on black rice molecular genetik diversity is an approach of DNA barcode. Most of the genes that utilized as DNA barcode on plants is on chloroplasts DNA (cpDNA). cpDNA having the benefit characteristics for genetik diversity study compared with nuclei DNA (nDNA ) and mitochondria mtDNA. Characteristic of these is (1) the cpDNA genome have a small size and stable structure, (2) More conservative with lower average nucleotide substitution and (3) no recombination and uniparental heritable. This article discussed a potential DNA sequences of nucleotides from chloroplast DNA to give information on the genetik diversity of black rice, namely rbcL gene. Until now, NCBI database collected 143 partial sequence of rbcL gene. The number of partial sequence that has been collected is using as comparation facilitate to investigation the genetik diversity of Indonesia black rice. In the future, DNA barcode os expected to be implemented in the research.Keywords: genetik diversity, DNA barcode,rbcL gene,Indonesian local black rice